Scanning electron microscopy as a method for sample visualization in protein X-ray crystallography. (2020) - Beale, Emma V.; Warren, Anna J.; Trinca˜o, Jose; Beilsten-Edmands, James; Crawshaw, Adam D.; Sutton, Geoff
No abstract available